Diabetes care and control: the effect of frequent visits to diabetes care center - Al Nozha, Omar Mansour (Ann Saudi Med, 2014)
BACKGROUND AND OBJECTIVES: Frequent visits to diabetes care clinics linked with better control of diabetes mellitus (DM), but debates exist about how frequently visits should be done. The objective of this study was to assess the effect of frequent visits on diabetes care and control. DESIGN AND SETTINGS: A prospective study of 100 diabetic patients attending Prince Abdul-Aziz Bin-Majed Diabetes Care Centre (PAMDCC), Al Madinah Al Munawwarah, Saudi Arabia, during the period from March 2011 through December 2012. METHODS: Demographics, lifestyle, and diabetes data were obtained at the index visit. At that and subsequent visits, glycosated hemoglobin (HBA1c), blood pressure (BP) and low-density lipoprotein (LDL) were measured. All these data together with visit number and gap were recorded. Statistical analysis including linear regression analysis was done. RESULTS: A significant reduction in the mean of diabetic control parameters was observed at the last visit. The highest mean changes were observed in patients with >6 visits, visit gap ≤1 month, and visit-month index ≥8. Adjusted linear regression showed that each visit significantly lowered HBA1c by 0.25%, BP by 2.1/0.7 mm Hg and 0.2 mmol/L for LDL. The number of visits needed to get HBA1c <7% and BP <130/85 was 8 and 5 visits with a visit-month index of 14 and 5, respectively. CONCLUSION: The study suggests that frequent visits at short intervals may lead to better diabetes control. Other prospective clinical trial studies are needed to confirm these findings and to outline the appropriate cost-effective intervals and visit gaps.